Pedagogical model for teaching Arabic-Malay transliteration intelligent tutoring system (ITS) - Qawqzeh, Yousef Kamel Oqla (2007)
Intelligent Tutoring System (ITS) considered as an important branch of Artificial Intelligent (AI) which can be used to assist in educational processes. Basically, some researchers divided ITS into four modules while others divided it into five modules. One of these modules is pedagogy module which concern in provide the educational processes especially teaching process by the needed knowledge (what to teach) and at the same time by providing some techniques or methods for teaching (how to teach). This project as its name implies concern in pedagogical module which care the process of teaching Arabic-Malay transliteration based on words level. It divided into two main quizzes which are words quiz and special quiz. Actually, both quizzes seen to be the same except that special quiz provides users with a complete transliteration at the end of each Ayah. This study was divided into seven chapters which are introduction, literature review, methodology, system analysis and design, evaluation, findings and results, conclusion and future recommendations